2012
DOI: 10.1051/0004-6361/201219696
|View full text |Cite
|
Sign up to set email alerts
|

The VMC Survey

Abstract: Context. The number and spatial distribution of confirmed quasi-stellar objects (QSOs) behind the Magellanic system is limited. This undermines their use as astrometric reference objects for different types of studies. Aims. We have searched for criteria to identify candidate QSOs using observations from the VISTA survey of the Magellanic Clouds system (VMC) that provides photometry in the Y JK s bands and 12 epochs in the K s band. Methods. The (Y − J) versus (J − K s ) diagram has been used to distinguish QS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 70 publications
1
32
0
Order By: Relevance
“…5.4, but there may be an additional effect due to the calibration using quasars and galaxies because the two types of objects have different mean colours (see e.g. Cioni et al 2013). Our proper motion for the SMC Red is dominated by stars in the red clump and RGB phases which typically have ages between 1 Gyr and a few Gyr.…”
Section: Comparison To Previous Measurementsmentioning
confidence: 96%
“…5.4, but there may be an additional effect due to the calibration using quasars and galaxies because the two types of objects have different mean colours (see e.g. Cioni et al 2013). Our proper motion for the SMC Red is dominated by stars in the red clump and RGB phases which typically have ages between 1 Gyr and a few Gyr.…”
Section: Comparison To Previous Measurementsmentioning
confidence: 96%
“…Field 1973;Vanden Berk et al 2001). Some of the background galaxies and QSOs identified in this study have been published in Cioni et al (2013). The full sample of background galaxies and QSOs will be discussed in a following publication.…”
Section: Preliminary Spectral Classificationmentioning
confidence: 99%
“…Some contamination from young stellar objects, brown dwarfs, planetary nebulae, and post-AGB stars is expected. Cioni et al (2013) estimated that the total number of quasars with Y < 19.32 mag, J < 19.09 mag, and K s < 18.04 mag is 1200 behind the LMC, 400 behind the SMC, 200 behind the Bridge, and 30 behind the Stream. Figure 1 shows the location of all confirmed quasars from the MQS and Table 1.…”
Section: Sample Selectionmentioning
confidence: 99%
“…The Magellanic Clouds system is an extreme case where these obstacles are notably enhanced: the combined area of the two galaxies, the Magellanic Bridge, and the Stream that connects them with the Milky Way is at least two hundred square degrees; the significant depth of the Small Magellanic Cloud (SMC) along the line of sight (e.g., de Grijs & Bono 2015) aggravates the contamination and reddening issues. Cioni et al (2013) reviewed previous works aiming at discovering quasars behind the Magellanic Clouds: Blanco & Heathcote (1986), Dobrzycki et al (2002Dobrzycki et al ( , 2003bDobrzycki et al ( ,a, 2005, Geha et al (2003), Kozłowski & Kochanek (2009), Kozłowski et al (2012), and Véron-Cetty & Véron (2010. In this study we add the latest installment of the Magellanic Quasar Survey (MQS) by Kozłowski et al (2013), who increased the number of spectroscopically confirmed quasars behind the Large Magellanic Cloud (LMC) and SMC to 758, almost an order of a magnitude higher than before.…”
Section: Introductionmentioning
confidence: 99%